Penguatan Kelembagaan Desa melalui Pendampingan Pengelolaan Keuangan Desa di Desa Jagabaya Kecamatan Warunggunung Kabupaten Lebak - Deni Permana (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Strengthening village institutions is the main prerequisite for realizing transparent, accountable, and participatory village governance. This community service activity aims to increase the capacity of the apparatus of Jagabaya Village, Warunggunung District, Lebak Regency, in managing village finances in accordance with the provisions of applicable laws and regulations. The main problems faced include the limited understanding of village officials in budget planning, administration, financial reporting, and the implementation of internal supervision. The activity was carried out using a participatory approach through training and technical assistance in village financial management. The results of the activity showed an increase in the understanding of village officials on the village financial management cycle which was reflected in the ability to prepare planning and budgeting documents more systematically, carry out financial administration using a standard format, and prepare accountability reports according to the provisions. This activity strengthens coordination between the village government, the Village Consultative Body (BPD), and the community in supervising the use of the budget, as well as increasing commitment to the principle of transparency through the publication of budget documents and village financial realization reports. This service activity contributes to strengthening village institutions and encouraging the realization of professional, accountable, and sustainable village governance.